2021
DOI: 10.1186/s40104-021-00617-8
|View full text |Cite
|
Sign up to set email alerts
|

Effects of supplemental xylanase and xylooligosaccharides on production performance and gut health variables of broiler chickens

Abstract: Background This study evaluated the effects of supplemental xylanase and xylooligosaccharides (XOS) in a corn-soybean meal (SBM)-based diet on growth performance and intestinal health of broilers. A total of 288 day-old chicks (Cobb 500) were allocated to 36 floor pens (8 birds/pen) equally in 9 dietary treatments in a 3 × 3 factorial arrangement. The treatments were combinations of 3 levels of xylanase (0, 0.005% and 0.01% Econase XT) and 3 levels of prebiotics (0, 0.005% and 0.01% XOS) added … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
33
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 47 publications
(35 citation statements)
references
References 43 publications
2
33
0
Order By: Relevance
“…It appeared that 50 mg/kg XOS was not sufficient to induce notable positive effects on SCFA production, or bird performance. This is in agreement with Singh et al. (2021) , who observed that total caecal SCFA concentration was increased when feeding 100 mg/kg XOS, but not 50 mg/kg XOS, and saw no improvements in performance with either level.…”
Section: Discussionsupporting
confidence: 92%
“…It appeared that 50 mg/kg XOS was not sufficient to induce notable positive effects on SCFA production, or bird performance. This is in agreement with Singh et al. (2021) , who observed that total caecal SCFA concentration was increased when feeding 100 mg/kg XOS, but not 50 mg/kg XOS, and saw no improvements in performance with either level.…”
Section: Discussionsupporting
confidence: 92%
“…Indeed, recently was shown that xylanase supplementation increased the abundance of Ruminococcaceae, Lachnospiraceae, and Lactobacillus salivarius [41]. The latter authors suggested that xylanase supplementation promoted broiler performance by improving feed efficiency and that these effects may be related to the increased abundance of beneficial gut microbiota [41]. A recent study [31] showed that supplementation of the same enzyme as in the current study in corn-based diets, stimulated Lactobacilli growth.…”
Section: Discussionmentioning
confidence: 48%
“…Lactic acid production could be related with abundance of beneficial gut microbiota such as Lactobacillus spp. Indeed, recently was shown that xylanase supplementation increased the abundance of Ruminococcaceae, Lachnospiraceae, and Lactobacillus salivarius [41]. The latter authors suggested that xylanase supplementation promoted broiler performance by improving feed efficiency and that these effects may be related to the increased abundance of beneficial gut microbiota [41].…”
Section: Discussionmentioning
confidence: 99%
“…Several researchers reported improved broiler body weight gain and FCR due to either probiotic supplementation alone or when combined with xylanase under diverse pathogen challenge models [ 35 , 36 ]. Furthermore, Singh et al [ 37 ] reported that xylanase supplementation promoted beneficial bacteria in the gut of broilers, which led to improved performance. This supports the hypothesis that a synergistic effect exists between xylanase and probiotics when combined.…”
Section: Discussionmentioning
confidence: 99%